Comparative Response Assessment of Steel Frames With Different Bracing Systems Under Seismic Effect. (August 2017) - Nassani, Dia Eddin; Hussein, Ali Khalid; Mohammed, Abbas Haraj
Abstract: The field of earthquake engineering and seismology is of a great importance to structural engineers around the world. Choosing an appropriate lateral force resisting system has a significant effect on performance of the steel structure. The paper presents a comparison of the seismic response of steel frames by using different types of bracing systems. The bracing systems are X-braced frames, V braced frames, inverted V braced frames, Knee braced frames and zipper braced frames. The steel frames are modeled and analyzed in four different height levels. Nonlinear static and dynamic analyses were performed. The frames consist of three bays and steel braces were inserted in the middle bay of each frame. The structural responses of frames are studied in terms of capacity curve, drift ratio, global damage index, base shear, storey displacements, roof displacement time history and plastification. The results showed a good improvement in the seismic resistance of frames with the incorporation of bracing. The results revealed that the bracing elements were very effective in diminishing drifts since the reduction of inter-storey drifts with respect to unbraced frames were on the average 58%. Also steel braces considerably reduced the global damage index.